PROVENANCE AND COMPOSITION OF THE BIMA GROUP EXPOSED AROUND WUYO VILLAGE, UPPER BENUE TROUGH N.E. NIGERIA - Zannah, Karagama Lawan; Hamza, Halidu; Ahmed, Isiaka I.; Alfa, Micheal P. (FUDMA Journal of Sciences, 2024)
Provenance study of Bima group of the Upper Benue Trough around Wuyo village was carried out on fresh representative samples. The petrographic results suggest the sandstones to be arkosic arenites, the average composition of the three rock forming minerals as observed are; 40% quartz, 46% feldspar and 3% rock fragments. The higher percentage of feldspar, the sphericity of the grain sizes which are largely sub-angular to sub-rounded and the poorly sorted nature of the sandstones as well as ZTR index of 60.3% from the heavy minerals analysis suggest immature sediments, they are deposited close to their source area. The coarse grain Sandstone in the study area were deposited by fluviatile system while the fine grain sandstone and clay were deposited in a lacustrine environment. The dominance of monocrystalline quartz as well as the Microscopic examination of the heavy minerals contained in the sandstones of the study area revealed that the sediments originated from dominantly granitic source and deposited by a moderate to high energy level shallow water continental conditions. The sutured contact, polycrystalline quartz crystals and the undulose extinction exhibited by some of the few quartz crystals in the petrographic studies is as a result of stress the sediment went through after deposition.
Keywords: Bima sandstone; Provenance; Upper Benue trough; Petrography; Heavy minerals